2011
DOI: 10.1111/j.1752-7325.2010.00201.x
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in dental services utilization among Brazilian low-income children: the role of individual determinants

Abstract: The conceptual framework has confirmed the presence of social and psychosocial inequalities on the utilization pattern of dental services for low-income children. The individual determinants seem to be important predictors of access.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
60
0
10

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(79 citation statements)
references
References 21 publications
(29 reference statements)
8
60
0
10
Order By: Relevance
“…Routine visit to the dentist was reported by half of adolescents, corroborating the findings of previous study conducted in Southeastern Brazil [30,31] Patients with eating disorders are more likely to hide and deny their condition, thus avoiding the help of health professionals [26]. After evaluating women aged 18 years or older with diagnosis of bulimia nervosa, US researchers found that the majority (70.8%) reported that they had not talked with oral health professionals about their problem, and the causes related to this barrier between patient and oral health professional were mainly embarrassment (81.1%), shame (77.6%) and fear (54.2%) [22].…”
Section: Discussionsupporting
confidence: 80%
“…Routine visit to the dentist was reported by half of adolescents, corroborating the findings of previous study conducted in Southeastern Brazil [30,31] Patients with eating disorders are more likely to hide and deny their condition, thus avoiding the help of health professionals [26]. After evaluating women aged 18 years or older with diagnosis of bulimia nervosa, US researchers found that the majority (70.8%) reported that they had not talked with oral health professionals about their problem, and the causes related to this barrier between patient and oral health professional were mainly embarrassment (81.1%), shame (77.6%) and fear (54.2%) [22].…”
Section: Discussionsupporting
confidence: 80%
“…This finding is similar to findings in other developing countries 22,23 , except Kenya, where higher figures have been reported 24 . Prior reports from Ile-Ife 15,25 , Ibadan 26 and Enugu 27 in Nigeria -all located in Southern Nigeria -had reported higher proportions of children utilizing dental care services.…”
Section: Discussionsupporting
confidence: 82%
“…Factors addressed by health geography studies investigating the dynamics of dental health disparities include the following: the geographical distribution of dental professionals 14,15,16,17 ; variables representing socioeconomic status 18,19,20,21,22,23 ; and lifestyle behaviors associated with poor oral health, such as consumption of sugared beverages and dental attendance patterns 16,24 .…”
Section: Introductionmentioning
confidence: 99%